Republic of Moldova Teachers : SABER Country Report 2014 - World Bank Group (World Bank, Washington, DC, 2015)
This report presents results of the application of SABER teachers in Moldova. It describes Moldova’s performance in each of the eight teacher policy goals, alongside comparative information from education systems that have consistently scored high results in international student achievement tests and have participated in SABER Teachers. Additional detailed descriptive information on Moldova’s and other education systems’ teacher policies can be found on the SABER teacher’s website. Data presented here are as of July 2014.